Time to stop the hand‐wringing. 'Net zero' hysterectomy is not an appropriate goal. (27th September 2022) - Nicklin, James
Abstract : Hysterectomy is an essential part of the treatment armamentarium for patients with malignant disease, severe prolapse, massive fibroids, with genetic mutations that predispose to endometrial cancer, and in selected patients with severe symptomatic endometriosis and adenomyosis. For patients with abnormal uterine bleeding unresponsive to non‐surgical measures, there is high‐level evidence that hysterectomy, particularly minimally invasive hysterectomy, is associated with higher rates of satisfaction and quality of life, comparable rates of serious adverse events and a lower incidence of further surgery, than endometrial resection or ablation. A 'net zero' hysterectomy is not an appropriate goal in contemporary gynaecological practice.